Impacto de las nuevas tecnologías para procesamiento y comunicación de datos en el desarrollo de la investigación social - Aigneren, Miguel (La Sociología en sus Escenarios, 2009)
Abstract . One of the most important signs of our time is the complex combinations among the different mass media. Referring to the New Information and Communication Technology (NTIC), people’s comments vary greatly in attitudes towards it. On the one hand, while the Internet and related information technologies, for example, may represent a very wide spectrum of possibilities for some people ; on the other, such a same technology may be offered resistance to by some others. However, the NTIC, and especially the Internet are just simply new tools and perhaps new ways of investigating. To access a virtual library will not mean anything to people if they do not know what to look for or how to evaluate what is found. To access and evaluate the information become then the basic issues if an investigation is worthy to be carried out. In other words, since we have entered a period in which the world is becoming a global and extended place, a place where the information becomes each second merchandise and a privileged tool, it is high time to teach accurately how to navigate and fish in the vast seas of information. Thus, it is essential to learn how to find it, evaluate it, and use it no matter the resources used in the process Resumen. Uno de los signos definitorios de nuestro tiempo es la existencia de complicadas combinaciones entre diferentes medios de comunicación. Cuando hablamos de las NTIC o Nuevas Tecnologías de la Información y la Comunicación, las posiciones varían desde quienes se entusiasman con las inmensas posibilidades de la red Internet o los multimedios, hasta aquellos que se resisten a estas tecnologías. Sin embargo, las NTIC, y especialmente la red Internet, son simplemente nuevas herramientas y quizás nuevos modos de investigar. El acceso a una biblioteca virtual no servirá de nada a quienes no saben qué buscar o como evaluar lo encontrado; el acceso y evaluación de la información son entonces puntos básicos para comenzar a trabajar cualquier proyecto investigativo. O sea que, en un mundo que se globaliza y extiende, donde la información es segundo a segundo mercancía y herramienta privilegiada es preciso enseñar a navegar y pescar certeramente en los extensos mares de la información. Aprender a encontrarla, evaluarla y usarla, es primordial, sin importar los recursos que se utilicen.